Research on Lateral Vibration and Load Sensitivity Reductions for Large-Scale Complex Nonconservative Systems Using Rigid-Flex Coupling Simulation Technique - Qi-bin Wang; Xing-jia Xu; Si-yang Piao; Chun-ge Nie; Qiu-ze Li; Ming-wei Piao (Shock and Vibration)
For large-scale complex nonconservative systems such as high-speed rolling stock, the rigid-flex coupling simulation technique is one of the effective methods in reducing lateral vibration and dynamic load sensitivity. Since two uncertain influences of wheel spin dissipation are caused by wheelset yaw oscillations and alternative load path variation due to nonstatically determined systems or redundant components/constraints, preliminary achievements of self-adaptive improved design make wheel–rail matching returns to rational conditions, managing and maintaining better data integrity of high-speed wheel–rail contact. A supporting platform was then established for multidisciplinary collaborative design optimization to scientifically promote the design speed, including inherent rigid-flex coupling relationship and integrity protection of nonconservative systems and associated individual structures. Combined with analysis results of long-term tracking online testing conclusions from Chinese practices of high-speed rails, relevant theoretical deductions find that the magnitude of quasistatic strain energy is one of the critical influencing factors in determining the dynamic interactions on coupling interfaces of interest. With this regard, two key technologies were further put forward, i.e., rational eigenstructure assignment based on modal modification responding technique and multiaxial weld fatigue damage assessment tool based on the correctness of modal stress recovery, both of which have been examined and verified in specific case investigations.